PROFIL BERPIKIR KREATIF SISWA BERKEPRIBADIAN KOLERIS DALAM MENYELESAIKAN SOAL ALJABAR - Shofiah, Ulfatus; Pambudi, Didik Sugeng; Trapsilasiwi, Dinawati; Sugiarti, Titik; Murtikusuma, Randi Pratama (Kadikma, 2019)
This study aims to analyze the stages of creative thinking of students with choleric personality types in solving Algebra problems. This type of research is qualitative research. Students with choleric personality types are given Algebra questions followed by interviews to explore information in students' creative thinking processes. The results obtained are students capable to form a mathematical model of the information contained in the problem using the Algebra symbol at the preparation stage. Students are capable to find more than one settlement idea by utilizing the equations formed in the problem and require a short time to understand the problem at the incubation stage. Students are capable to write the completion steps containing Algebra operations systematically at the illumination stage. Students are capable to recheck the answers generated by substitute the value of the variable sought into an equation well at the illumination stage. The conclusion of this study is that choleric students are capable to fulfill all the indicators at the Wallas creative thinking stage. This can be seen from the results of the Algebra test given and the results of the interviews that have been conducted.